1968
DOI: 10.1107/s0567739468000094
|View full text |Cite
|
Sign up to set email alerts
|

Many-beam dynamical theory of the line in the middle of a Kikuchi band

Abstract: The unindexed line which runs along the middle line of a Kikuchi band is explained in the case of the 200 band from magnesium oxide by the theory of Kikuchi patterns [Kainuma, Acta Cryst. (1955) 8, 247]. The intensity profile across the line is estimated without solving the equation of the dispersion surface, by using a matrix formulation of the many-beam dynamical theory. In the estimation, the 000, 200 and 400 reflexions of elastically scattered waves and the ~00, 000 and 200 reflexions of inelastically scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Lines which cannot be indexed as ordinary Kikuchi lines can also be observed in the middle of Kikuchi bands, as shown by e.g. Kainuma and Kogiso [3]. These, usually asymmetric lines resemble the displaced lines observed in [I, 21 being displaced a reciprocal vector f g from the f 2 g lines.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Lines which cannot be indexed as ordinary Kikuchi lines can also be observed in the middle of Kikuchi bands, as shown by e.g. Kainuma and Kogiso [3]. These, usually asymmetric lines resemble the displaced lines observed in [I, 21 being displaced a reciprocal vector f g from the f 2 g lines.…”
Section: Introductionmentioning
confidence: 83%
“…12, i.e. the case discussed in[3].Calculated systematic line contrast for g = 1 1 1 in Si corresponding to Pig. 4.…”
mentioning
confidence: 91%
“…The filament current was reduced I 800 IiormalKikuchi lines which are either white (excess) or black (deficient) this line has an asymmetrical whitelblack (excess-deficient) profile. Kainuma and Kogiso [14] have examined this line and shown that its asymmetrical profile depends on the sign, and its intensity depends on the magnitude of Uk Q. The importance of this line in the experimental determination of the critical voltage can now be appreciated, since as noted in the Introduction, on passing through U , the parameter U i s changes sign, becoming zero at U,.…”
Section: Measurement Of Critical Voltagementioning
confidence: 92%
“…The theory of Kikuchi patterns was originated by Kainuma (1955), and it has been applied to interpret the fine details observed in Kikuchi patterns (Fujimoto and Kainuma, 1963;Kainuma and Kogiso, 1968;Okamoto et at, 1971). The theory proposed by Kainuma (1955) involves equations analogous to the Yoshioka equations, which are solved in a proper Bloch wave representation to find the angular distribution of inelastically scattered electrons at the exit face of the crystal.…”
Section: Theory Of Kikuchi Patternsmentioning
confidence: 99%